جهود المنظّمات الدوليّة في حفظ السّلم والأمن الدوليين - مدلل, حفناوي (جامعة الوادي University of Eloued, 2015)
يتناول موضوع هذا البحث دور وجهود المنظّمات الدوليّة في حفظ وإرساء السّلم والأمن الدوليين على اعتبار أنّ هذه الأخيرة تُعنى بالتنسيق بين أعضائها من الدّول حيث تلجأ المنظّمات الدوليّة إلى ما يُمكن أن نسمّيه وسيلة النّصح والإقناع لتشجيع أعضائها لحلّ منازعاتهم بالطّرق السّلمية وذلك عن طريق مختلف الأعمال القانونيّة التي تصدر عنها, كالقرارات والتوصيات والإعلانات والتّوجيهات. Abstract: Addresses the subject the role and efforts of international organizations in maintaining peace and international security on the basis that these organizations are working on coordination among its members states. Where these international organizations go to what we might call the way of advice and persuasion to encourage their members to resolve their differences through peaceful means, through various legal actions emanating from them, such as resolutions, recommendations and declarations and instructions…
Keywords: المنظمات الدوليّة؛ السلم؛ الأمن الدولي؛ مبدأ حفظ السلم؛ النصح والإقناع؛ الطّرق السلميّة؛ المنازعات؛ التوصيات